y=x(2)-2x+3

Simple and best practice solution for y=x(2)-2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=x(2)-2x+3 equation:


Simplifying
y = x(2) + -2x + 3

Reorder the terms for easier multiplication:
y = 2x + -2x + 3

Reorder the terms:
y = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
y = 3 + 0
y = 3

Solving
y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 3

See similar equations:

| 2k-10-7=8 | | 5(-2x-4)=97+3(4x+5) | | logx+log(4x-3)=1 | | 13=x^2-14x | | 32w-8w+21=69 | | 9y-15=-3(y+7) | | 22590-x=17500 | | 46t-9t+7t-40t+12=96 | | T(x)=2x^2+8x+6 | | 7x+12y=1 | | 62=5x | | 6p+14q= | | 4k+k-2k+8=86 | | 25-8x=1 | | -2p+24=13 | | 5x+8=6x-21 | | 92m-62m-23m-4m-m+7=95 | | 45-14y=5+6y | | 15=-4d+3 | | 39k-21k-6k-4k-7k=42 | | 14-4y=10 | | (2+y)(5y-4)=0 | | 5a+2=-18 | | 1.25x+12y=60 | | 3=-7k+3 | | -6f+8=2 | | 21=4b-7 | | 5(2x-3)=11 | | 8k-4=4 | | 3x-10=10-x | | 7n+9=2 | | 2g-g=97 |

Equations solver categories